A review of C/EBP α: a potential novel target for solid tumor intervention - Xin Li; Tengkun Dai; Jiamin Zhao; Yidan Liang; Longqing Chen; Chao Chen; Mengmeng Guo; Yong Han; Lin Xu; Juanjuan Zhao (Journal of Translational Medicine)
Abstract C/EBPα (CCAAT enhancer binding protein) is a pivotal transcription factor with widespread expression in multiple tissues, including hematopoietic tissues, liver, lungs, mammary glands, skin, and adipose tissue. It plays a significant role in the developmental regulation of these tissues. Previous research has primarily concentrated on C/EBPα’s involvement in the hematological system, particularly its role in maintaining human hematopoietic stem cell homeostasis and regulating myeloid differentiation. Notably, recent studies have revealed that C/EBPα is instrumental in the development and therapeutic targeting of solid tumors. Abnormal expression of C/EBPα has been observed in various tumor types, such as liver, breast, pancreatic, gastric, and lung cancers, where it regulates tumor cell proliferation, differentiation, and other processes through signaling pathways including EGFR/β-catenin, Wnt, and so on. Moreover, the expression levels of C/EBPα are closely associated with the clinical prognosis of these solid tumors. These findings suggest that C/EBPα may serve as a promising new target for clinical interventions against solid tumors. In this paper, we systematically review the structure, function, and expression regulation mechanism of C/EBPα. We also discuss its biological functions in solid tumors such as breast, liver, and pancreatic cancers, along with key scientific issues that need to be addressed in future studies, our aim is to provide new perspectives and robust support for the in-depth elucidation of the biological function of C/EBPα, and for the development of new strategies for the clinical treatment of solid tumors.